2011
DOI: 10.1007/s11417-011-9115-x
|View full text |Cite
|
Sign up to set email alerts
|

Reintegrative Shaming and Juvenile Delinquency in Japan

Abstract: The Japanese juvenile justice system has been widely regarded as operating based on the principles of reintegrative shaming. Reintegrative shaming, as opposed to a stigmatizing form of shaming, communicates disapproval of wrongdoing with respect, and emphasizes rehabilitation, reintegration, and restoration. Central to reintegrative shaming at the initial contact point of the criminal justice system in Japan are apology and diversion by the local police. Citing juvenile delinquency cases reported in a major na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Their findings indicated that reintegrative shaming functioned for juvenile delinquency because the involvement of significant others was more likely to result in 'less state intervention and more utilisation of informal social control' (Sakiyama, Lu & Liang, 2011: 172). Therefore, while they admitted the limitations of their research, particularly in the use of involving significant others as a proxy of reintegrative shaming, they suggested that reintegrative shaming is partially effective in the Japanese (juvenile) justice system (Sakiyama, Lu & Liang, 2011). …”
Section: Applicability Of Reintegrative Shaming At the Institutional mentioning
confidence: 99%
“…Their findings indicated that reintegrative shaming functioned for juvenile delinquency because the involvement of significant others was more likely to result in 'less state intervention and more utilisation of informal social control' (Sakiyama, Lu & Liang, 2011: 172). Therefore, while they admitted the limitations of their research, particularly in the use of involving significant others as a proxy of reintegrative shaming, they suggested that reintegrative shaming is partially effective in the Japanese (juvenile) justice system (Sakiyama, Lu & Liang, 2011). …”
Section: Applicability Of Reintegrative Shaming At the Institutional mentioning
confidence: 99%
“…The former relies on condemnation of the act as well as the individual, while the latter focuses on the act rather than the individual and offers opportunities for the targeted actor to rejoin the community. 7 This distinction informs the discussions of academics and practitioners over the merits of punitive steps against offenders as opposed to paths of restorative and transitional justice (e.g., Hannem-Kish 2004;Sakiyama, et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…In her study of the everyday lives of girls detained in the Hong Kong Kwai Chung Girl’s [sic] home, Chan Mei-wan (1988) also demonstrates how the home’s system of rewards and punishments encourages social conformity. Expanding upon John Braithwaite’s theory of reintegrative shaming, Sakiyama et al (2011: 166) use the case of juvenile offenders in Japan to illustrate the cultural context of deviance prevention in a society that values social conformity and communitarian living. Seeking forgiveness through apologies is expected in Japan to the extent that those who have committed a criminal act are expected to seek forgiveness from the parties harmed by that act (Smith and Sueda, 2008).…”
Section: Introductionmentioning
confidence: 99%